Analysis of ventricular repolarization parameters and heart rate variability in obesity: a comparative study - Akash Tomar; Himani Ahluwalia; H. S. Isser; Sameer Gulati; Puneet Kumar; Indrajeet Yadav (Scientific Reports)
Abstract Obesity is associated with dysfunctional electrocardiographic and cardiac autonomic parameters, which may lead to increased cardiovascular morbidity. Novel electrocardiographic repolarization markers such as Tpeak-Tend (Tpe) interval have not yet been deeply studied in obese patients. We aimed to investigate the association between ventricular repolarization parameters and heart rate variability (HRV) and how they are affected by changes occurring in the cardiac autonomic nervous system. Ninety subjects categorized by Southeast Asian BMI (kg/m2) standards - normal (18-22.9), overweight (23-24.9), and obese (> 24.9), underwent assessment of ventricular repolarization parameters and HRV. Linear correlation between different parameters was also conducted. Obese subjects exhibited longer QTc and Tpe intervals compared to normal-weight subjects (p-value < 0.001, 0.026 respectively). The QTc interval showed a significant correlation (p < 0.05) with all HRV parameters by linear correlation, while the Tpe interval did not. Anthropometric parameters (BMI, WC, and WHR) were also correlated to both ventricular repolarization variables and HRV. While changes in the QTc interval may be due to obesity and/or autonomic changes occurring in the obese state, the Tpe interval does not show a relation with autonomic parameters. Thus, implicating that a change in the Tpe interval is primarily due to the direct effect of either cardiac or visceral obesity. The observed associations between ECG parameters, obesity indices, and HRV parameters suggest a role for ECG in screening for cardiovascular morbidity.